Pengaruh Gadget Terhadap Perilaku Anak Kelas VI SD IT Al-Maqom - Putri Auliya; Suci Padilah Sukmawati; Sri Mulyeni (Universitas Maritim AMNI Semarang, 2025)
The purpose of this study is to find out how the behavior of students at SD IT Al-Maqom in relation to gadgets. Along with technological advances, the use of gadgets has become an important aspect of daily life, even for students. This study uses quantitative methodology using direct regression method, involving 70 students as samples.Data were collected through the distribution of questionnaires that measure the influence of gadgets on the behavior of students.The results of the analysis show that the use of gadgets has a significant influence on the behavior of students of SD IT Al-maqom, with a level of influence of 76.3%.Although gadgets have a considerable impact, this study also realizes that other factors such as environment, parenting style, and genetic factors also influence the behavior of students, although these factors are not examined in this study.The conclusion is that gadgets have a significant influence on the behavior of students of SD IT Al-Maqom.